Determinants of Islamic Commercial Bank Performance in Indonesia - Rizal, Fitra; Mukaromah, Haniatul (Indonesian Journal of Islamic Economics and Finance, 2023)
As financial intermediary institutions, banks have a strategic role in driving the economy, so bank performance must be appropriately maintained. This study aims to analyze the effect of third-party funds and working capital financing of Islamic commercial banks on the performance of Islamic commercial banks in Indonesia. The research method used is quantitative by conducting multiple linear regression tests. The data type used is secondary data from 2015 to 2022, with a sample of 13 Islamic commercial banks in Indonesia. The data was obtained from BI and OJK reports published on https//www.ojk.go.id. The study results indicate that Third Party Funds do not affect Indonesia's ROA of Islamic commercial banks. Working capital financing significantly affects the ROA of Islamic commercial banks in Indonesia. And if together, third-party funds and working capital financing significantly affect the ROA of Islamic commercial banks in Indonesia. Third-party funds do not affect the ROA of Islamic general banks because the operational costs (BOPO) borne by Islamic general banks are included in the very high category. Therefore, to increase ROA, banks must apply the principle of prudence and valid calculations in carrying out banking operations and financing.